2017
DOI: 10.1186/s12879-017-2211-5
|View full text |Cite
|
Sign up to set email alerts
|

Smear positive pulmonary tuberculosis and associated risk factors among tuberculosis suspects attending spiritual holy water sites in Northwest Ethiopia

Abstract: BackgroundTuberculosis (TB) remains one of the world’s deadliest communicable diseases. In Ethiopia, tuberculosis patients have different pattern of health care seeking behavior. They usually adopt other approaches like traditional healers and spiritual holy water sites before consulting public health facilities. This study was aimed to assess the prevalence of smear positive pulmonary tuberculosis and associated risk factors among tuberculosis suspects attending spiritual holy water sites.MethodsA cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
35
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 22 publications
5
35
3
Order By: Relevance
“…The levels of awareness of patients regarding tuberculosis in general and pulmonary tuberculosis were similar to those reported in other studies [20, 21]. Majority of the patients first either practiced self-medication or visited traditional healers; these findings were consistent with those of other studies from rural areas [22, 23]. Such health care-seeking behavior of patients causes complications [10, 20]; this finding emphasizes the need for improved public awareness about EPTB [3, 24].…”
Section: Discussionsupporting
confidence: 89%
“…The levels of awareness of patients regarding tuberculosis in general and pulmonary tuberculosis were similar to those reported in other studies [20, 21]. Majority of the patients first either practiced self-medication or visited traditional healers; these findings were consistent with those of other studies from rural areas [22, 23]. Such health care-seeking behavior of patients causes complications [10, 20]; this finding emphasizes the need for improved public awareness about EPTB [3, 24].…”
Section: Discussionsupporting
confidence: 89%
“…The study also revealed that TB patients delayed seeking health care from the health facilities while receiving care from the informal health care providers. Similar findings were documented in Ethiopia [38], Malawi [39], Tanzania [40], Nepal [41] and Ghana [42]. These providers are crucial in the referral system necessary for timely TB diagnosis and should be educated on the importance of referring patients with a prolonged cough for a TB test even as they continue offering their therapy.…”
Section: Discussionsupporting
confidence: 67%
“…Due to the absence of published evidences on TB prevalence among shopkeepers, the author tried to discuss present prevalence with studies at the community, facility, and prison levels in Ethiopia; since they have some similarities, they are relatively higher, risky/congregated settings/to acquire TB infection [ 13 ]. The current prevalence was found to be higher compared to study findings from Dessie and Debre-Birhan (among homeless participants) [ 5 ], people attending spiritual holy water services as the alternative medication to their illnesses [ 10 ], and North Gondar [ 12 , 14 ] where TB prevalence was 2.6%, 2.9%, 5.3%, and 4.9%, respectively. The possible explanation for this variation could be differences in area coverage, comorbidity prevalence, information access, contact status with TB patients, and overcrowdedness.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, education level (illiteracy), working inside the nonventilated rooms, low awareness of TB transmission, and comorbidity with other chronic diseases such as HIV/AIDS and DM were statistically significant factors to acquire TB infection among shopkeepers ( Table 2 ). All these were reported challenges to the END TB program in 2015 by the WHO [ 2 ] and other studies [ 5 10 ].…”
Section: Discussionmentioning
confidence: 99%